The effect of high-protein snack consumption during hemodialysis on nutrient intake and nutritional status in patients with stage V chronic kidney disease - Ayu Andalia; Ahmad Syauqy; Diana Nur Afifah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Protein-energy wasting (PEW) in hemodialysis patients can cause weight loss, muscle mass, physical strength, and biochemistry. Adequate protein intake during hemodialysis is essential to reduce catabolic effects and improve nutritional status. This study aimed to analyze the effects of high-protein snack consumption on nutrient intake (energy, protein, fat, carbohydrate, sodium, potassium, and phosphorus), nutritional status (BMI, Hb, and muscle mass), and handgrip strength. Methods: This study was conducted from August to September 2024 at Alimuddin Umar Hospital in West Lampung using a quasi-experimental design with a control group of 30 patients with chronic kidney disease (CKD). The intervention group received high-protein snacks (18 g/session), whereas the control group received low-protein snacks (<12 g/session) for six weeks. Nutrient intake was assessed using 24-hour recall, handgrip strength was measured using a camera dynamometer, and nutritional status was analyzed using anthropometric and biochemical parameters. The results showed an increase in nutrient (energy, p = 0,036; protein, p = 0,000; fat, p = 0,000; carbohydrate, p = 0,040; sodium, p = 0,010; potassium, p = 0,043; phosphorus, p = 0,001), Hb (p = 0,001), and urea (p = 0,015) intake, There were no changes in BMI (p= 0,836), muscle mass (p= 0,575), creatinine level (p= 0,183), or handgrip strength (p= 0,899) in patients with CKD. In conclusion, high-protein snacks used during hemodialysis can improve nutrient intake and clinical parameters in patients with CKD.